1988
DOI: 10.1111/j.1365-2559.1988.tb01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intestinal pseudo‐obstruction in two patients. Overlap of features of systemic sclerosis and visceral myopathy

Abstract: Two patients with chronic intestinal pseudo-obstruction are reported, one of whom had definite systemic sclerosis while the other had certain manifestations of the disease. Biopsies of the small intestine revealed increased collagen and elastic fibres in the muscularis propria and subserosa in each case, while ganglion cells were normal. In addition, one patient had severe atrophy of the inner muscle layer and the other obvious vacuolation of the muscularis propria. Ultrastructural examination confirmed degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
2
3
0
Order By: Relevance
“…On the basis that PAS-positive inclusions were only found in cases of gastrointestinal dysmotility in this study, and that such inclusions have only previously been reported by others [4,20,21] in similar conditions, it seems likely that they would be of some significance. On the basis that PAS-positive inclusions were only found in cases of gastrointestinal dysmotility in this study, and that such inclusions have only previously been reported by others [4,20,21] in similar conditions, it seems likely that they would be of some significance.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…On the basis that PAS-positive inclusions were only found in cases of gastrointestinal dysmotility in this study, and that such inclusions have only previously been reported by others [4,20,21] in similar conditions, it seems likely that they would be of some significance. On the basis that PAS-positive inclusions were only found in cases of gastrointestinal dysmotility in this study, and that such inclusions have only previously been reported by others [4,20,21] in similar conditions, it seems likely that they would be of some significance.…”
Section: Discussionsupporting
confidence: 79%
“…The characteristic pathological features of this disorder were highlighted by PAS staining, with ovoid inclusion bodies, 2-30 µm in length, demonstrated. Similar or perhaps identical inclusion bodies have been reported in three patients with intestinal pseudo-obstruction and visceral myopathy, which was either idiopathic (two patients: colonic inclusions) [4] or found (a single case) in association with a probable diagnosis of scleroderma (ileal inclusions) [20,21]. Similar or perhaps identical inclusion bodies have been reported in three patients with intestinal pseudo-obstruction and visceral myopathy, which was either idiopathic (two patients: colonic inclusions) [4] or found (a single case) in association with a probable diagnosis of scleroderma (ileal inclusions) [20,21].…”
Section: Introductionsupporting
confidence: 66%
“…These are thought to resemble polyglucosan inclusion bodies found in other polysaccharide storage diseases in both skeletal [11] and smooth [12] muscle as well as in the gastrointestinal tract of aging dogs [13]. Vacuolar degeneration of the smooth muscle of the gastrointestinal tract is a characteristic feature of more widespread visceral myopathy [14] as well as of chronic intestinal pseudo-obstruction [15], although in each of these disorders there is smooth muscle degeneration rather than hypertrophy and no inclusions in the vacuoles. Another recent case [10] has shown pathological variance of this condition with similar ultrastructural changes in the absence of inclusion bodies.…”
Section: Discussionmentioning
confidence: 94%
“…However, routine histology in these disorders only identifies the most severe degrees of fibrosis, myocyte atrophy and smooth muscle vacuolation, and more subtle morphological abnormalities or intrinsic cellular defects may remain undetected unless ultrastructural or immunohistochemical studies are performed 7,11,15,[17][18][19][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%